Emergence of power and complexity in obstetric teamwork - Neuhaus, Christopher; Lutnæs, Dag Erik; Bergström, Johan (PLOS ONE, 2022)
Background Recently, increasing attention has been paid to team processes in peripartum care settings with the aim to improve fetomaternal outcomes. However, we have yet to understand how the perception of teamwork in peripartum care is shaped in a complex, multi-disciplinary environment. Methods The aim of this study was to approach the question using qualitative social-scientific methodology. The theoretical foundation of the study was that obstetric teamwork is the result of a balancing act in which multiple goal conflicts are continuously negotiated and managed right at the boundary of acceptable performance in a complex adaptive system. We explored this theory by gathering lived experiences of successful management of peripartum emergencies. Based on our analysis we generated an understanding of teamwork as a phenomenon emerging from interpersonal relationships, complex relations of power, and the enactment of current quality management practices. Results Caregivers define teamwork through the quality of their collaboration, defined by respect and appreciation, open communication, role distribution, and shared experiences. However, teamwork also becomes the framework for negotiation of many conflicts that originated elsewhere. Power was the core theme that emerged in the analysis of our participants’ narratives, which is in stark contrast to the otherwise promoted egalitarian rhetoric of team training. While our participants generally reverted to explanations based on their professional identities, traditions or cultures, interesting dynamics become visible when work is viewed through the power lens. Conclusions Our study paints the convoluted picture of a work environment with all its intricacies, constraints, interpersonal relations and hierarchical struggles that are much more representative of a complex system rather than the easily tractable environment that so many stakeholders would like healthcare practitioners to believe in. The issue of power emerged as a decisive factor in the social dynamics at the workplace, revealing hidden agendas in the teamwork discourse.